MANAJEMEN PELAYANAN PENANGGULANGAN HIV/AIDS DALAM UPAYA SCREENING DI PUSKESMAS TEMAYANG KABUPATEN BOJONEGORO - jurnalpps pps; Dwi Ripnowati; Cathrine Sri Hartati; Gurendro Putro (Prodi Magister Manajemen Universitas Wijaya Putra, 2019)
ABSTRACT The purpose of this research is to analyze the service management process, the factors that support and inhibit service management, and the management strategy of HIV/AIDS prevention services in the screening effort conducted by Temayang Health Center of Bojonegoro Regency. This research is a qualitative research to analyze the quality of HIV/AIDS prevention services conducted by Puskesmas Temayang Bojonegoro District. Primary data were obtained from interviews with doctors, laboratory officers, village midwives, village nurses, and DHO officers. The result of the research stated that first, the form of management functions that have been done by Puskesmas Temayang in tackling HIV/AIDS disease as a screening effort are: Planning, Organizing, Actuating, Control (supervision). Secondly, the factors that support and obstruct the program are: Internal factors include, lack of extension media, insufficient funding resources, inadequate facilities and infrastructure; External factors, including misunderstanding among the public about screening HIV / AIDS, reluctant people are present in extension activities and health checks related to HIV / AIDS, the provision of a limited examination room. Third, management strategy is done by doing cross-sectoral cooperation which involves three main element that is element of Government, Community element, and element of youth. Keywords: management, HIV/AIDS prevention, screening